Ubuntu as a spirituality of liberation for black theology of liberation - Kobe, Sandiswa L. (HTS teologiese studies, 2021)
This article aims to respond to Vuyani Vellem’s challenge to black theology of liberation (BTL) to ‘think beyond rethinking and repeating its tried and tested ways of responding to black pain caused by racism and colonialism’. Vellem argued that ‘BTL needs to unthink the west by focusing on and retaining African spirituality as a cognitive spirituality’ for the liberation of black people in South Africa. This article argues that Ubuntu is the spirituality of liberation that BTL needs to advance as one of its interlocutors. This research work will consult the literature emerging from African philosophy, ethics, spirituality and BTL arguing that Ubuntu is an indigenous philosophy, spirituality that continues to exist in the languages and culture of the Abantu (Bantu) speaking people. This article is dedicated to the memory of Vellem as a BTL scholar and a faithful believer of the liberative paradigms of BTL.Contribution: The scholarly contribution of this article is its focus on the systematic and practical reflection, within a paradigm in which the intersection of religious studies, social sciences and humanities generate an interdisciplinary contested discourse.